Intervention for Children with Neurodevelopmental Disorders: Narrative Review - Nath, Ankita; Banerjee, Sonali; Kumar Roy, Prasanta (Journal of Neonatal Surgery, 2025)
Neurodevelopmental disorder (NDD) is a world-wide public health issue that particularly affects children in low- and middle-income countries. Early diagnosis, intervention, and rehabilitation are primary ways to aid children's functioning skills according to their diverse needs with neurodevelopmental disorders (NDD) and also those of their parents. The WHO’s International Classification of Functioning, Disability, and Health (ICF) Framework focuses on a child’s health beyond biomedical deficits, using the concept of functioning to measure development concerning this construct. In case of ICF-CY which was developed for children and youth but measurement tool is difficult to understand to be used for children, also CFM developed by UNICEF, is a gross tool for children. This narrative review aims to identify early participatory intervention measures for children with NDD that are based on the ICF, as described in the literature. Incorporating with this ICF framework many researchers have introduced intervention to the children with NDD but still there is a huge gap for screening and early intervention at baseline level. This review used a systematic search procedure with various health-related databases (Frontiers, research gate, PubMed, google scholar), and identified family focused intervention that provide support to children with NDD in paediatric health in different settings. In India, approximately 2.3 million children below six years of age group have some developmental disability, and many of them are from rural and semi-urban areas with minimum access to early intervention services. Results showed that the children with NDD who participated in those interventions showed improvement in all domains with both the intensive and regular services. It was also observed that including parents’ participation in therapy sessions enhanced the programme outcomes. Participation and activities are the most common ICF domains, as per the framework.